MATRIKS INVERS MOORE PENROSE ATAS DAERAH INTEGRAL - SRRM, Titi udjiani (MATEMATIKA, 2005)
The Inverse Moore Penrose matrix has been applied in various areas, for example in statistic and optimization. In this paper we study Inverse Moore Penrose matrix which is applied to Integral Domain. We will first discuss the characterization of all matrices over Integral Domain which admits Moore Penrose Inverse. With this characterization we will deriveÂ necessary and sufficient conditions for a matrix to have a Moore Penrose Inverse. We also show the relations between Moore Penrose Inverse matrix and Compound matrix. The aim of this paper is to obtain an explicit formula for the Moore Penrose Inverse when it exist and gives a necessary and sufficient condition for a matrix to have a Moore Penrose Inverse under the assumption that a matrix has a rank factorization. Â